Penerapan Diabetes Self-Management Education (DSME) Melalui Media Leaflet Interaktif - Hamdan Hariawan; Suardi Zurimi; Martini Tidore (Jurnal Nasional Pengabdian Masyarakat, 2020)
The prevalence of non-communicable diseases such as diabetes mellitus continues to increase every year. The incidence of its complications also increases if not given the right action as a form of prevention. One form of management and prevention of complications of diabetes mellitus is to improve patient self-care. One of the factors that affect the self-care of diabetes mellitus patients is the communication of health workers towards the self-care of DM sufferers. The output was the implementation of DSME socialization activities and the implementation of DSME by Health Center officers to diabetes mellitus patients through interactive leaflet media. The results of this Community Service are in the form of socialization to health center officers regarding how to conduct Diabetes Self-Management Education (DSME) using interactive leaflet media. The application of DSME socialization is in the form of counseling to health center officers about DSME which contains self-care for diabetes mellitus patients which includes an explanation of the definition of diabetes, causes, management, and prevention of complications.